Peeking and lying in the temptation resistance paradigm in 2.5-year-olds: The role of inhibitory control - Białecka-Pikul, Marta; Białek, Arkadiusz; Stępień-Nycz, Małgorzata; Talwar, Victoria; Bosacki, Sandra (PLOS ONE, 2022)
The main aim of the present study was to establish whether inhibitory control (IC) abilities influence the peeking and lying behaviours of 2.5-year-olds, as measured by a modified temptation resistance paradigm (mTRP). Using a longitudinal design, 252 children’s IC abilities were tested at ages 1.5, 2 and 2.5, as well as their ability to lie at age 2.5. Results showed that 35% of 2.5-year-olds peeked, 27% of peekers lied and 40% of non-peekers falsely confessed they had peeked. Non-peekers had higher IC than peekers at ages 2 and 2.5. Lower IC at age 2 increased the probability of peeking at age 2.5 by 6 times. The highest level of IC was presented in children who followed the adult’s restrictions in the mTRP and were then able to tell the truth about their behaviour. These results suggested that the first, or so-called primary, lies of 2.5-year-olds are probably spontaneous, rather than deliberate. Implications for further research were discussed.